2007
DOI: 10.1021/ja0686256
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Azumamide E Histone Deacetylases Inhibitory Activity

Abstract: Azumamide E, a cyclotetrapeptide isolated from the sponge Mycale izuensis, is the most powerful carboxylic acid containing natural histone deacetylase (HDAC) inhibitor known to date. In this paper, we describe design and synthesis of two stereochemical variants of the natural product. These compounds have allowed us to clarify the influence of side chain topology on the HDAC-inhibitory activity. The present contribution also reveals the identity of the recognition pattern between azumamides and the histone dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 41 publications
0
78
0
Order By: Relevance
“…20 Like the aminobenzamides, cyclic peptides are reportedly class I-selective. [21][22][23] To date, no class I-selective compounds have been reported that demonstrate a high degree (Ͼ100ϫ) of selectivity between HDAC1 and HDAC2, which share nearly identical catalytic domains. Facilitated by the solution of the human HDAC8 crystal structure, 24 selective hydroxamate inhibitors of this distinct class I subfamily member have recently emerged.…”
Section: Hdaci Structural Classes and Selectivitymentioning
confidence: 99%
“…20 Like the aminobenzamides, cyclic peptides are reportedly class I-selective. [21][22][23] To date, no class I-selective compounds have been reported that demonstrate a high degree (Ͼ100ϫ) of selectivity between HDAC1 and HDAC2, which share nearly identical catalytic domains. Facilitated by the solution of the human HDAC8 crystal structure, 24 selective hydroxamate inhibitors of this distinct class I subfamily member have recently emerged.…”
Section: Hdaci Structural Classes and Selectivitymentioning
confidence: 99%
“…Because these large and diverse capping groups are believed to provide significant interactions with amino acid residues on the surface of the enzyme, members of the cyclic peptides or macrocyclic family of HDACi can possess a variety of ZBG (Fig. 8), including thiols (FK-228, largazole [75]), hydroxamic acids (compound 18 [76]), ketones (apicidin [77] (azumamide E [78]), and α-epoxy ketones (chlamydocin [79], trapoxin B [80]). …”
Section: Cyclic Peptides and Other Macrocyclesmentioning
confidence: 99%
“…For example, trapoxin B (an irreversible α-epoxy ketone) exhibits a 640-fold selectivity for HDAC1 vs HDAC6 with picomolar potency on HDAC1 (IC 50 =110 pM) [80]. In 2007, Maulucci et al [78] reported a series of cyclic tetrapetides, the azumamides, of which the most selective analog, azumamide E, displayed 100-fold selectivity for HDACs 1, 2, and 3 (50-100 nM) vs all other HDAC isoforms. Similarily, apicidin, another cyclic tetrapeptide possessing a ketone-based ZBG, showed preferential selectivity for HDACs 1, 2, 3, and 8 over all other HDAC isoforms [53].…”
Section: Cyclic Peptides and Other Macrocyclesmentioning
confidence: 99%
“…12 ■ RESULTS AND DISCUSSION Building Block Synthesis. For our synthesis of the β-amino acid building block, we chose a diastereoselective Ellman-type Mannich reaction to set the stereochemistry, as also previously reported by Ganesan and co-workers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…g Determined by comparison of spectroscopic data of the fully elaborated Boc-protected β-amino acid with previously reported data. 12 Figure 2. X-ray crystal structure of the (2S,3S) precursor obtained by desilylation of the major product in entry 5 of Table 1.…”
Section: ■ Introductionmentioning
confidence: 99%